A National Study of Oncology Nurses Discussing Cancer Clinical Trials With Patients. (December 2019) - Flocke, Susan A.; Nock, Nora L.; Fulton, Sarah; Margevicius, Seunghee; Manne, Sharon; Meropol, Neal J.; Daly, Barbara J.
In the United States less than 10% of cancer patients engage in clinical trials. Although most oncology nurses have multiple opportunities to discuss clinical trials with patients, barriers including attitudes and social norms may impede these discussions. Guided by the Theory of Planned Behavior, we developed and evaluated measures for attitudes, subjective norms, and perceived behavioral control of nurses for discussing clinical trials with cancer patients. Of the 18, 000 Oncology Nurse Society members invited, 1, 964 completed the survey. Structural equation modeling and internal consistency reliability were used to evaluate items and constructs. We found that overall model fit and reliability was good: Confirmatory Fit Index (CFI) = 0.91, Root Mean Square Error of Approximation (RMSEA) = 0.05; attitudes, 21 items, alpha = 0.84; perceived behavioral control, 10 items, alpha = 0.85; and subjective norms, 9 items, alpha = 0.89. These measures of attitudes, subjective norms, and perceived behavioral control show good reliability and initial evidence of validity.